Implementation of SWOT Analysis in the Implementation of the Independent Curriculum and Independent Teaching Platform in the Super Smart Society 5.0 Era - Sifak, Sifak; Hadi, Irfan; Suharyati, Henny (Journal of Industrial Engineering & Management Research, 2024)
If Indonesian Human Resources are designed to seize and win the Super Smart Society 5.0 Era, with very tight competition at the global level, it is inevitable that from an early age HR must be equipped with the supporting capabilities to face it. Education from childhood is a key factor in preparing tough and competitive human resources, where the curriculum has an important role, through continuous curriculum development is one answer to meeting the required competencies. The free learning curriculum and free teaching platform launched by the government are specifically designed to provide the right to learn freely. The aim of this research is to find out and analyze how the independent curriculum and independent teaching platform are implemented in the Super Smart Society 5.0 Era. To get an overview of the Merdeka Curriculum and the Merdeka Teaching Platform, the Systematic Literature Review (SLR) Method is used, while to find out the implementation strategy, use the SWOT analysis approach, namely an analysis that reads strengths, weaknesses, opportunities and threats. With this analytical model, we can find the right steps for implementing an independent curriculum and an independent teaching platform.